2003
DOI: 10.1016/s0953-5438(03)00036-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving web search on small screen devices

Abstract: Small handheld devices-mobile phones, Pocket PCs etc.-are increasingly being used to access the web. Search engines are the most used web services and are an important factor of user support. Search engine providers have begun to offer their services on the small screen. This paper presents a detailed evaluation of the how easy to use such services are in these new contexts. An experiment was carried out to compare users' abilities to complete search tasks using a mobile phone-sized, handheld computer-sized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 17 publications
4
45
0
1
Order By: Relevance
“…Jones et al [3] evaluated users' abilities on mobile phones, PDAs, and desktop interfaces for some of the earliest mobile search systems. They found that both the search speed and accuracy were worse on smaller screens.…”
Section: Mobile Search Behaviourmentioning
confidence: 99%
“…Jones et al [3] evaluated users' abilities on mobile phones, PDAs, and desktop interfaces for some of the earliest mobile search systems. They found that both the search speed and accuracy were worse on smaller screens.…”
Section: Mobile Search Behaviourmentioning
confidence: 99%
“…With the proliferation of mobile phones and PDAs, small screen devices are now pervasive, but smaller screens can make even basic tasks such as reading and web browsing more difficult [9,19]. The reduced screen size means that, even with high resolution screens, designers must choose only the most important features to display.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, users tend to use mobile devices in contexts where their attention is limited in comparison to traditional environments [24], which may make it more difficult to navigate a complex interface. To address the limitations of small screen devices, several researchers have proposed that adaptive interfaces, where the system tailors the interface to an individual user's needs, may be beneficial [2,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, we have to live with them because these natural limitations arise from the fact that most mobile devices need to be, by definition, small and mobile. Studies on Web page searching on mobile devices (Jones et al, 1999;Jones et al, 2003), though not specifically on photo searching, form a useful starting point for searching within a mobile photo management context; ideas for visualization on mobile devices have been proposed, especially for displaying interactive maps for location-based navigation (Chittaro, 2006). The minimal attention user interface (MAUI) (Pascoe et al, 2000) tries to design a mobile interface that requires minimal user attention.…”
Section: Designing Mobile Interface For Photo Managementmentioning
confidence: 99%